Myoelectrically Controlled FES to Enhance Tenodesis Grip in People With Cervical Spinal Cord Lesion: A Usability Study - Thorsen, Rune; Dalla Costa, Davide; Beghi, Ettore; Ferrarin, Maurizio (Frontiers in Neuroscience, 2020)
The hand of many people having sustained tetraplegia is often without adequate grip strength for activities of daily living. Research has demonstrated that the hand function can be improved by a virtual tendon transfer, using myoelectrically controlled functional electrical stimulation (MeCFES). Together with 79 persons having cervical spinal cord injury (C5-C7), we assessed the feasibility of this technique for overcoming limitations in activities of daily living. For the research, a single channel prototype capable of simultaneous stimulation and electromyographic recording with wired connections to two pairs of surface (transcutaneous) electrodes, was produced. Twenty-seven participants found the MeCFES device effective and functional as it had a direct orthotic effect on grip strength. They agreed to test the method in a clinical setting with 12 occupational therapy sessions of 2 hours each, performing relevant self selected activities. The outcome measures were validated questionnaires, the Individually Prioritised Problem Assessment (IPPA) and the Quebec User Evaluation of Satisfaction with Assistive Technology (QUEST) together with a question about Usefulness. All participants had functional benefits evinced by all having a significant (p<0.0001) IPPA change score of 4.6 (SD:3.5, effect size:1.3) and 14 subjects found the system useful. A therapeutic effect was also found as the participants acquired new abilities, probably due to training and intrinsic muscle strengthening. We report the ranking of the chosen activities and outcomes with respect to the level of lesion. The QUEST indicates that further effort in development should address wearability, eliminate wires and improve the fitting procedure.